Development of a Chemistry Module on Buffer Solutions Using Dual Representations Assisted by Animation - Nasir*, Muhammad; Hasan, Muhammad; Adlim, Adlim; Fazli, Rahmat Rizki; Utari, Fitri Diah; Syukri, Muhammad; Khwaengmek, Wipavadee (Jurnal Pendidikan Sains Indonesia, 2024)
Buffer solutions are a crucial concept in chemistry that students often find difficult to grasp. An effective method to enhance students' understanding is through the use of dual representations assisted by animation. Dual representations involve using various forms of visualization, such as diagrams, graphs, and animations, to help students comprehend abstract concepts more effectively. The research type employed is research and development (RD) using a 4-D model consisting of four stages: define, design, develop, and disseminate. The research subjects were 26 students from class XII MIPA 1 SMA Negeri 5 Banda Aceh. Data collection techniques were conducted by distributing questionnaires for student needs analysis, module and animation feasibility assessment, educator response to modules and animations, and student understanding tests. The developed module obtained very good assessment results from 2 validators with an average percentage of 89.16%, while the animation media received very good assessment results with an average percentage of 80.43%. Educators' responses to modules and animations were categorized as very good, with percentages of 94.17 and 95.84% respectively. Students' responses were also categorized as very good with an average percentage of 87.2%. The results of students' understanding were categorized as good with an overall score of 82.60%. Based on the results of this research, it is concluded that the animation-assisted multiple representation module on buffer solution material is highly suitable for use as teaching material in the learning process